Charge storage characteristics of gold nanoparticles embedded in alumina matrix - Bratus, O.; Evtukh, A.; Kaganovich, E.; Kizjak, A.; Kizjak, I.; Manoilov, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The processes of charge accumulation in the nonvolatile memory metal-oxidesilicon
capacitors with gold nanoparticles floating gate formed by the pulsed laser
deposition method are investigated. The regularities of formation of alumina films with
gold nanoparticles are the result of their deposition from the back flow of low-energy
particles from the erosion torch. With removing from the torch axis, sizes of gold
particles and the film thickness decreased. When recording the capacitance-voltage
curves, the capture of a negative charge was observed. It was shown that the
concentration of gold nanoparticles in alumina matrix and the thickness of
nanocomposite films remarkably influenced on the stored charge. The observed flat band
voltage shift was in the range 1 to 14 V. To explain the peculiarities of charge storage in
the composite films, the electron transport through them was investigated.